Electrochemical performance of A-site substituted SmSrNiO4−δ for energy storage applications - Chauhan M.; Bangwal A.S.; Singh P. (My University, 2025)
In this work, a series of Ruddlesden popper oxide materials Sm1−xLaxSr1−xCaxNiO4−δ (x = 0.00, 0.05, 0.10, 0.15, and 0.20) were synthesized and their electrochemical behavior was investigated in 1 M KOH alkaline solution. Phase formation in all the samples is confirmed through XRD. SEM depicts the porous morphology of all the samples. FTIR confirms the presence of –OOH and –OH groups in several compositions. The Cyclic voltammetry curve of Sm0.90La0.10Sr0.90Ca0.10NiO4−δ and Sm0.80La0.20Sr0.80Ca0.20NiO4−δ indicates the presence of the combination of both pseudo-capacitance and electrochemical double-layer capacitance in these two electrodes. However, only the sample Sm0.90La0.10tSr0.90Ca0.10NiO4−δ sample satisfies the condition of the general power law for pseudo capacitance. This material also shows the highest value of specific capacitance (910.20 F/g) and electrochemical double-layer capacitance (238.25 mF/cm2) among all the samples. XPS analysis reveals that oxidation states of the Nickel and Oxygen play a crucial role for the better electrochemical performance of the electrode. © 2022 Hydrogen Energy Publications LLC